THE VIEWS OF RELIGIOUS COURT JUDGES IN NORTH SUMATRA REGARDING INTELLECTUAL PROPERTY ROYALTIES REMAINING JOINT PROPERTY AFTER DIVORCE - Syahran Camil; Ibnu Radwan Siddik Turnip (Program Pascasarjana UIN Sumatera Utara, 2025)
The status of Intellectual Property Rights (IPR) royalties as joint property after divorce remains a matter of debate among academics and legal practitioners due to the lack of clear regulations in positive law or the Compilation of Islamic Law (KHI). This article aims to examine the views of judges at the Religious Court of North Sumatra regarding IPR royalties remaining as joint property after divorce. This study uses empirical juridical research with a statutory approach, case studies, and a conceptual approach. Primary data sources were obtained from interviews with several Religious Court judges domiciled in North Sumatra. Secondary data sources were obtained from primary legal materials such as Law Number 28 of 2014 concerning Copyright and Law Number 13 of 2016 concerning Patents. Data analysis used qualitative analysis methods. The results show that the views of Religious Court judges in North Sumatra regarding the distribution of IPR royalties after divorce are very diverse, reflecting a spectrum of thought from moderate to restrictive. Some judges argue that the approach to distributing royalties from intellectual works, such as songs, is based on the principle of moderate justice. The 50:50 distribution scheme is considered a basic rule or default rule that reflects the balance of rights between both parties during the marriage. However, this rule is not absolute; the distribution can be adjusted if there is evidence that one party has made a greater contribution, whether financially, through creative ideas, or through administrative support. Some judges reject the distribution of intellectual property royalties after a divorce, in order to maintain the principle of creator autonomy, unless there is a clear prenuptial agreement. In other words, intellectual property rights cannot simply be categorized as joint property without a clear contractual legal basis. Others prefer a contextual approach, assessing each case uniquely based on the economic structure, relationship history, and contributions of each party.